Relationship between Serum Interferon Gamma Level with Sputum Positivity of Acid-Fast Bacillus in New Case Pulmonary Tuberculosis - Andi Khomeini Takdir; Erwin Arief; Nur Ahmad Tabri; Arifin Seweng (Jurnal Penyakit Dalam Indonesia)
Introduction. Interferon gamma (IFN-γ) is an important cytokine to eliminate M. tuberculosis. Level of IFN-γ in tuberculosis (TB) patients increase in the beginning of disease and will decrease after therapy. This study aims to know the association between IFN-γ serum level and acid-fast bacilli (AFB) sputum positivity.